2021
DOI: 10.2147/jhc.s325593
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets of Ferroptosis in Hepatocellular Carcinoma

Abstract: Ferroptosis is a special form of regulatory cell death caused by the accumulation of intracellular iron and lipid peroxidation. Here, we summarize the research progress on ferroptosis in hepatocellular carcinoma (HCC), trace the development of the concept of ferroptosis and its key regulatory factors, and discuss the application value of ferroptosis in the treatment of HCC from different perspectives. We believe that exploring the relationship between ferroptosis and HCC and clarifying the metabolism and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…Although such preclinical data suggest a promising anticancer approach via the induction of ferroptosis, clinical studies are currently not available and the usage of ferroptosis inducing substances need to be further studied in situ [ 43 , 48 ]. Preclinical data regarding hepatocellular carcinoma demonstrate a promising outlook to combat liver cancer with the induction of ferroptosis [ 49 , 50 ]. The following chapter discusses the conceptual background why ferroptosis might be especially attractive for novel approaches in HCC treatment.…”
Section: The Potential Of Ferroptosis In (Hepatocellular) Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although such preclinical data suggest a promising anticancer approach via the induction of ferroptosis, clinical studies are currently not available and the usage of ferroptosis inducing substances need to be further studied in situ [ 43 , 48 ]. Preclinical data regarding hepatocellular carcinoma demonstrate a promising outlook to combat liver cancer with the induction of ferroptosis [ 49 , 50 ]. The following chapter discusses the conceptual background why ferroptosis might be especially attractive for novel approaches in HCC treatment.…”
Section: The Potential Of Ferroptosis In (Hepatocellular) Cancer Therapymentioning
confidence: 99%
“…In HCC, ferroptosis might play a different role compared to other forms of liver diseases. Several studies demonstrated that iron overload in HCC is a driver of tumorigenesis, proliferation and tumor growth [ 49 , 67 ]. Therefore, one approach of anticancer therapy might be the maintenance or increase of abnormal iron levels in HCC cells in order to induce overproduction of ROS resulting in ferroptotic cell death.…”
Section: The Potential Of Ferroptosis In (Hepatocellular) Cancer Therapymentioning
confidence: 99%
“…It may not involve a direct kinase inhibition and/or binding to an alternative target such as an unknown kinase whose activity is necessary for system x c − [161]. Besides inhibiting tumor proliferation through the RAF/MEK/ERK signaling pathway, sorafenib can block tumor angiogenesis via VEGFR and platelet-derived growth factor receptor (PDGFR) [162]. Sorafenib-induced ferroptotic anticancer activity can be enhanced by blocking another critical regulator named metallothionein (MT)-1G that also plays an antioxidant role [163].…”
Section: Fin56mentioning
confidence: 99%
“…NRF2 is involved in iron and ROS metabolism, where it protects HCC cells against ferroptosis through upregulation of multiple genes such as HMOX1 [122]. The common leucine zipper transcription factor NRF2 is essential for redox homeostasis and regulates the metabolism of multiple cancer cells, which makes it a promising target for tumor therapy [162]. Several studies have assessed the role of NRF2 in ferroptosis, and upregulation of iron and ROS by genetic or pharmacological inhibition of NRF2 expression leads to an enhanced anti-tumor effect of erastin and sorafenib [153].…”
Section: Targeting Nrfmentioning
confidence: 99%
“…On the other hand, immunogenic deaths, ferroptosis, and pyroptosis can result in immune responses due to the release of various intracellular contents, most acting as pro-inflammatory signals. Though the role of ferroptosis and pyroptosis in HCC prognosis had been previously discussed ( 6 , 7 ), how non-immunogenic apoptosis as well as immunogenic ferroptosis and pyroptosis cross-talk at the gene and protein levels and collaboratively contribute to the development of the immunosuppressive HCC TME remain to be further addressed.…”
Section: Introductionmentioning
confidence: 99%